Evaluating conserved domains and motifs of decapod gonadotropin-releasing hormone G protein-coupled receptor superfamily - Buckley, Sean J.; Nguyen, Tuan Viet; Cummins, Scott F.; Elizur, Abigail; Fitzgibbon, Quinn P.; Smith, Gregory S.; Mykles, Donald L.; Ventura, Tomer (Frontiers in Endocrinology, 2024)
G protein-coupled receptors (GPCRs) are an ancient family of signal transducers that are both abundant and consequential in metazoan endocrinology. The evolutionary history and function of the GPCRs of the decapod superfamilies of gonadotropin-releasing hormone (GnRH) are yet to be fully elucidated.As part of which, the use of traditional phylogenetics and the recycling of a diminutive set of misannotated databases has proven insufficient. To address this, we have collated and revised eight existing and three novel GPCR repertoires for GnRH of decapod species. We developed a novel bioinformatic workflow that included clustering analysis to capture likely GnRH receptor-like proteins, followed by phylogenetic analysis of the seven transmembrane-spanning domains. A high degree of conservation of the sequences and topology of the domains and motifs allowed the identification of species-specific variation (up to ~70%, especially in the extracellular loops) that is thought to be influential to ligand-binding and function. Given the key functional role of the DRY motif across GPCRs, the classification of receptors based on the variation of this motif can be universally applied to resolve cryptic GPCR families, as was achieved in this work. Our results contribute to the resolution of the evolutionary history of invertebrate GnRH receptors and inform the design of bioassays in their deorphanization and functional annotation.